2018
DOI: 10.1016/j.ajoc.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of chronic corneal opacity in ocular surface disease with prosthetic replacement of the ocular surface ecosystem (PROSE) treatment

Abstract: PurposeTo demonstrate clearing of chronic corneal opacities and improvement of visual acuity with the use of BostonSight prosthetic replacement of the ocular surface ecosystem (PROSE) treatment in ocular surface disease.ObservationsWe undertook retrospective analysis of the medical records of a series of patients who underwent PROSE treatment from August 2006 to December 2014. Patients were referred for ocular surface disease of various etiologies. Primary inclusion criterion was corneal opacity that improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…There has been a dramatic increase in the number of scleral publications from 2012 to 2016 compared to the previous 5-year period based on a recent study on the body of scleral lens-related scientific research [1]. Recent literature includes single-center, retrospective case series which generally describe a single lens design and unified fitting philosophy [2][3][4][5][6][7]. Studies on observed or potential impact of scleral lenses on ocular surface structures have also been published within the past 5 years [8,9], as has research on the structure and contour of conjunctival, episcleral, and scleral tissue [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a dramatic increase in the number of scleral publications from 2012 to 2016 compared to the previous 5-year period based on a recent study on the body of scleral lens-related scientific research [1]. Recent literature includes single-center, retrospective case series which generally describe a single lens design and unified fitting philosophy [2][3][4][5][6][7]. Studies on observed or potential impact of scleral lenses on ocular surface structures have also been published within the past 5 years [8,9], as has research on the structure and contour of conjunctival, episcleral, and scleral tissue [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Scleral lens use may provide a similar therapeutic effect with better social acceptance. It was previously reported that in cases of neurotrophic keratitis, scleral lenses not only provide protection and facilitate ocular surface healing [19] but may also decrease the degree of chronic corneal opacification [20]. One of the main adverse effects of SL wear is corneal hypoxia and edema [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overflow of liquid hydrogels from the site of the defect, if not carefully controlled, may prevent epithelial migration over the hydrogel 26 . Filling the defect would make it easy to individualize the various morphologies of corneal defects, and negating the irregular astigmatism by providing a smooth refracting surface is expected to improve vision even with the persistent corneal opacity of scarring 27 . In vitro, we found that the underlying letter was readable in both 0.4% and 0.8% of PEG-collagen hydrogel.…”
Section: Discussionmentioning
confidence: 99%